1972
DOI: 10.1002/jsfa.2740230315
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of laboratory ensiling techniques

Abstract: Silages made from 18 grasses and 8 legumes in test-tube silos holding 100 g of fresh herbage were compared with those from the same crops ensiled in PVC bags holding 1 tonne of fresh material. For 8 herbages, polythene bags holding 6 kg of fresh material were also employed. Measurement of pH, ammonia-N, lactic acid and volatile acids was made at the end of the storage period (64-155 days). Measurements made on silages from the test-tube silos were closely correlated with those from the PVC bags. The correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 16 publications
2
36
0
Order By: Relevance
“…Previous research has indicated that the size and type of laboratory silos, as well as the amount of forage ensiled, have little effect on silage fermentation. Wilson and Wilkins (1972) compared silages made from 18 grasses and eight legumes, produced in PVC bags, test-tubes and polythene bag silos, containing respectively 1 t, 100 g and 6 kg of forage, and concluded that the fermentation profile in the three types of silos agreed closely. Rodrigues et al (2002) did not detect differences in major fermentation parameters (pH, N-NH 3 , volatile fatty acids, lactic acid) and DML when comparing corn silages produced in plastic buckets (12 L), plastic bags (40 L) and concrete pipes (630 L).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has indicated that the size and type of laboratory silos, as well as the amount of forage ensiled, have little effect on silage fermentation. Wilson and Wilkins (1972) compared silages made from 18 grasses and eight legumes, produced in PVC bags, test-tubes and polythene bag silos, containing respectively 1 t, 100 g and 6 kg of forage, and concluded that the fermentation profile in the three types of silos agreed closely. Rodrigues et al (2002) did not detect differences in major fermentation parameters (pH, N-NH 3 , volatile fatty acids, lactic acid) and DML when comparing corn silages produced in plastic buckets (12 L), plastic bags (40 L) and concrete pipes (630 L).…”
Section: Resultsmentioning
confidence: 98%
“…The usefulness of laboratory silos in forage conservation research has been long established (Wilson and Wilkins, 1972), but studies on the effects of differences in laboratory silos on silage fermentation are scarce (O'Kiely andWilson, 1991 in Cherney et al, 2004;Rodrigues et al, 2002;Cherney et al, 2004). Analysis of fermentation products is normally carried out in water extracts produced in a blender or stomacher and, less frequently, in silage juices produced by the use of a hydraulic press.…”
Section: Introductionmentioning
confidence: 99%
“…Water-soluble carbohydrate was determined in freeze-dried samples by the alkaline-ferricyanide method of Hagedorn & Jensen (1923) adapted for use with a Technicon Autoanalyser. The micro-diffusion method of Conway (1957) was used for ammonia determination, VFA were determined by gas-liquid chromatography (Wilson & Wilkins, 1972) and lactic acid by eerie sulphate oxidation (Elsden & Gibson, 1954). Chromium and calcium were determined by atomic absorption spectroscopy, sodium and potassium by flame photometry and phosphorus by a colorimetric method using vanado-molybdate.…”
Section: Methodsmentioning
confidence: 99%
“…The lactic acid content of the extract was determined by the ceric sulphate oxidation method,5 ammonia content by a micro-diffusion technique6 and volatile fatty acids (VFA) by g.l.c. 3 Samples of fresh forages were taken for pH, dry matter (DM), WSC and total nitrogen (TN) determinations. DM was determined by oven-drying for 16 h at lOO"C, WSC as for the silages and TN by a Technicon method involving alkaline phenate as colorimetric reagent.…”
Section: Methodsmentioning
confidence: 99%